Strategi Pembelajaran Berdiferensiasi Meningkatkan Kemampuan Literasi Membaca Pemahaman Siswa - Adi Pratama (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2022)
The purpose of this study is to describe the improvement of literacy skills in reading comprehension through the application of differentiated learning strategies for fifth-grade elementary school students in reading and learning habits in the classroom. The method used is a qualitative approach with a descriptive method. In a case study in class 5 SDN Larangan 2, Cirebon City The academic year 2021-2022 face-to-face learning is limited. The results showed that the differentiated learning strategy was able to improve the literacy skills of 5th-grade elementary school students.